Feedback Matters : Evidence from Agricultural Services - Jones, Maria Ruth; Kondylis, Florence (World Bank, Washington, DC, 2016)
Feedback tools have become ubiquitous in the service industry and social development programs alike. This study designed a field experiment to test whether eliciting feedback can empower users and increase demand for a service. The study randomly assigned different feedback tools in the context of an agricultural service to document their impact on clients' demand and shed light on the underlying mechanisms. The analysis shows large demand effects, in the current and following growing periods. It also documents large demand effect spillovers, as other non-client farmers in the vicinity of treated groups are more likely to sign up for the service. To disentangle pure supply-side monitoring from demand-side accountability effects, additional monitoring was randomly announced to extension workers across treatment and control communities. Extension workers do not exert significantly more effort in villages where additional monitoring takes place. The study concludes that farmers’ taste for "respect" leads their higher demand for the service.